Pre-melt-season sediment plume variability at Jökulsárlón, Iceland, a preliminary evaluation using in-situ spectroradiometry and satellite imagery. Issue 73 (12th May 2016) - Hodgkins, Richard; Bryant, Robert; Darlington, Eleanor; Brandon, Mark
ABSTRACT: High-latitude atmospheric warming is impacting freshwater cycling, requiring techniques for monitoring the hydrology of sparsely-gauged regions. The submarine runoff of tidewater glaciers presents a particular challenge. We evaluate the utility of Moderate Resolution Imaging Spectroradiometer (MODIS) imagery for monitoring turbid meltwater plume variability in the glacier lagoon Jökulsárlón, Iceland, for a short interval before the onset of the main melt season. Total Suspended Solids concentrations ( TSS ) of surface waters are related to remotely-sensed reflectance via empirical calibration between in-situ-sampled TSS and reflectance in a MODIS band 1-equivalent wavelength window. This study differs from previous ones in its application to an overturning tidewater glacier plume, rather than one derived from river runoff. The linear calibration improves on previous studies by facilitating a wider range of plume metrics than areal extent, notably pixel-by-pixel TSS values. Increasing values of minimum plume TSS over the study interval credibly represent rising overall turbidity in the lagoon as melting accumulates. Plume extent responds principally to consistently-strong offshore winds. Further work is required to determine the temporal persistence of the calibration, but remote plume observation holds promise for monitoring hydrological outputs from ungauged or ungaugeable systems.